An optimized Al2O3 layer for enhancing the anode performance of NiCo2O4 nanosheets for sodium-ion batteries. Issue 34 (3rd July 2017) - Kou, Huari; Li, Xifei; Shan, Hui; Fan, Linlin; Yan, Bo; Li, Dejun
Abstract : Herein, an ultrathin Al2 O3 layer was coated onto NiCo2 O4 nanosheets via an atomic layer deposition (ALD) method, and the NiCo2 O4 coated with an ALD-derived Al2 O3 material was successfully used as an anode material for sodium-ion batteries (SIBs). Abstract : Herein, an ultrathin Al2 O3 layer was coated onto NiCo2 O4 nanosheets via an atomic layer deposition (ALD) method, and the NiCo2 O4 coated with an ALD-derived Al2 O3 material was successfully used as an anode material for sodium-ion batteries (SIBs). This kind of electrode exhibited enhanced cycling performance with a reversible capacity of 395 mA h g −1 after 50 cycles, and good rate capability with the discharge capacities of 350, 320, and 294 mA h g −1 at the various current densities of 100, 200, and 400 mA g −1, respectively. Interestingly, remarkable prevention of the reactions between the electrode and electrolyte was observed. The performance improvement is due to the protection of the NiCo2 O4 coated with an ALD-derived Al2 O3 layer from the electrochemical active materials. These results demonstrate the great potential of NiCo2 O4 coated with an ALD-derived Al2 O3 material as anodes in SIBs.